PENGAKUAN HUKUM TERHADAP HAK ULAYAT MASYARAKAT HUKUM ADAT - Hidayat Hidayat (to-ra, 2015)
Recognition of the existence of customary rights by Article 3 of the Basic Agrarian Law is a natural thing, because along with the customary rights of indigenous communities have existed before the formation of the state of Republic Indonesia. However, many cases of communal land which arise in the regional and national scale, will never obtain settlement completely without any objective criteria necessary as a benchmark determinants of the existence of customary rights and their implementation. Criteria for deciding about the existence of customary rights is composed of three elements, namely the existence of a particular customary law community, the presence of certain customary rights into the environment and the purpose of taking the lives of indigenous people, and the existence of customary law regarding the maintenance of order, control and use lands which apply and be adhered to by the indigenous peoples. Metode of reserach is juridis normative. The results of reaserach shows that there is no regulatory of customary right, and the rule is still from the society. The rule of customary right can be gap to customary rights, in fact lowest.Kata Kunci : Pengakuan hukum, Hak ulayat Masyarakat Hukum Adat